Enhanced radiosensitivity of head and neck cancer cells to proton therapy via hyperthermia-induced homologous recombination deficiency - Tim Heemskerk; Gerarda van de Kamp; Marta Rovituso; Roland Kanaar; Jeroen Essers (Clinical and Translational Radiation Oncology)
Background and purpose: Radiotherapy induces tumor cell killing by generating DNA double strand breaks (DSBs). The effectiveness of radiotherapy is significantly influenced by the repair of DSBs, which counteracts this lethal effect. Current investigations are focused on determining whether non-homologous end joining (NHEJ) or homologous recombination is the predominant repair pathway following proton and photon radiation. Materials and methods: In this study, we examined the response of FaDu cells, a head and neck squamous cell carcinoma model, to spread-out Bragg peak (SOBP) proton and photon radiation combined with mild hyperthermia (42 °C for one hour) to induce homologous recombination deficiency or NHEJ inhibition by AZD7648. Results: Hyperthermia resulted in stronger radiosensitization after proton radiation (SR = 1.53) compared to photon radiation (SR = 1.32). Conversely, NHEJ inhibition did not produce a significant differential effect between photon and proton radiation. This indicates a greater reliance on homologous recombination following proton radiation compared to photon radiation. We found that the number of DSBs formed after photon versus proton irradiation is comparable. Interestingly, the homologous recombination protein Rad51 accumulated more frequently at DSBs following proton irradiation than photon irradiation. Conclusions: These findings support the hypothesis that cells rely more on homologous recombination to repair proton-induced DNA damage compared to photon-induced DNA damage. As clinically applied hyperthermia enhances the therapeutic effect of photon irradiation by, among other factors, inducing homologous recombination deficiency, our results suggests that hyperthermia could be more effective in combination with proton irradiation than photon irradiation.